(untitled) (Research, Society and Development, 2021)
This essay aims to explain about the place occupied by Brazil in the process of capital accumulation in times of crisis, contextualizing the political coup of 2016, that ousted the democratically elected president and installed a reformist government to enable the illusory-utopian strategies of US international capital. The approach proposed here is based on analyses in the light of historical-dialectical materialism, which enable the apprehension of the real beyond the immediate visible and on bibliographic and documentary reviews by authors who carry out the critique of capitalist society. The study is based on Marx and on authors who have analyzed the process of capital accumulation, productive restructuring, the crises of capitalism and the current situation of the working class, and on documents produced from the political context-socioeconomic at this moment in Brazilian history. The investigation revealed that the coup that resulted in barbarism against the poorest and the working class through reforms in the Brazilian state apparatus, spreading as an illusion of economic prosperity, actually conditioned the working class to various levels of job insecurity, either by throwing workers into informality or legitimizing the exploitation of labor. The illusion of market utopias finally resulted in increased unemployment, precarious work.